Efektivitas Model Think Pair Share Berbantuan Media Kartu Analisis terhadap Hasil Belajar Ekonomi Siswa - Syahlaa Haafizhah Gumilar; Ai Nur Solihat (Lembaga Pengembangan Kinerja Dosen, 2026)
Learning outcomes in economics at SMA Al Muttaqin Tasikmalaya were still below the expected learning achievement criteria due to the limited use of student-centered learning models. This study aimed to examine the effectiveness of the Think Pair Share (TPS) cooperative learning model assisted by analysis card media in improving students' economics learning outcomes. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of Grade XI students, with Class XI-7 as the experimental group and Class XI-8 as the control group. Data were collected through pretests, posttests, observation, and documentation. The data were analyzed using descriptive statistics, normality and homogeneity tests, paired sample t-test, independent sample t-test, and normalized gain (N-Gain). The findings revealed significant differences between pretest and posttest scores in the experimental class. Furthermore, students taught using the Think Pair Share model assisted by analysis card media achieved significantly higher learning outcomes than those taught through conventional learning. The experimental class also demonstrated a higher N-Gain score, indicating greater improvement in learning outcomes. These findings suggest that integrating the Think Pair Share model with analysis card media effectively enhances students' engagement and improves economics learning outcomes. The study recommends implementing this instructional model as an alternative strategy to foster active learning and improve academic achievement in economics education.